ANALYSIS OF THE COST OF PRODUCTION AND PROFITABILITY OF MANUFACTURE OF PELLETS (THE CASE OF MINA SENTOSA) IN THE VILLAGE OF LENGGADAI HULU DISTRICT OF RIMBA MELINTANG ROKAN HILIR IN RIAU PROVINCE - Adi Syahputra; Lamun Bathara; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was carried out in June 2015 in Mina Sentosa business pellets which located in the village of Lenggadai Hulu district of Rimba Melintang Rokan Hilir in Riau Province. The purpose of this research is to know the cost of the investment, Production Costs, acceptance and gains obtained at the Mina Sentosa pellets business. The methods used in the research is case studies. Total investment was issued as much as Rp 74,520,000.0-with production cost incurred amounting to Rp 24,201,500.0-/month. Admissions obtained as much as Rp 28,800,000.0-/Month. So that obtained net income as much as Rp 4,598,500.0-/month. The business analysis of the research shows that the business was profitably with the value of the RCR 1.19.Keywords: Investment, Production Costs, The Rate Of Profit, Mina Sentosa